2013
DOI: 10.1684/epd.2013.0624
|View full text |Cite
|
Sign up to set email alerts
|

Ictal swearing: a case series and review

Abstract: Seizures can manifest with ictal swearing but few studies have investigated the localising value of this epileptic manifestation. In this case series and review of the literature, we attempted to determine whether ictal swearing could help localise the epileptic focus. We review two previously published cases and report eight additional epileptic patients with ictal swearing for whom the epileptic focus was determined based on clinical, structural, electrophysiological, and surgical outcome data. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Ictal swearing is more common among males, with lateralization to the non-dominant hemisphere. 2,4,6 However, Massot-Tarrús et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ictal swearing is more common among males, with lateralization to the non-dominant hemisphere. 2,4,6 However, Massot-Tarrús et al…”
Section: Discussionmentioning
confidence: 99%
“…4 This implies a different neurophysiological process between ictal swearing and ictal speech. 2,5 Ictal speech results from activation or inhibition of language cortical function, whereas the hypothesized mechanism of ictal swearing is the dysregulation of emotional and behavioral function. 4 In this context, limbic frontal-temporal networks can produce ictal swearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally men swear more than women. Men with epilepsy might swear during seizures more than women with epilepsy (Birca et al, 2013).…”
Section: Ictal Swearing/coprolaliamentioning
confidence: 97%
“…Recently, the largest case series of ictal swearing has been published that reviewed two old case reports of ictal swearing and presented 8 new cases. Results indicated that ictal swearing occurs more commonly in male subjects and lateralizes to the non-dominant hemisphere, but has poor localization value, arising either from the frontal, parietal, temporal or occipital lobes in different patients (Birca et al, 2013). Another case report of ictal swearing and aggression in FLE also lateralizes to the non-dominant hemisphere (Shih et al, 2009).…”
Section: Ictal Swearing/coprolaliamentioning
confidence: 97%